Modifiers of heterocyst repression and spacing and formation of heterocysts without nitrogenase in the cyanobacterium Anabaena variabilis. - Rogerson, A C (1979)
Twelve amino acid analogs and related compounds were screened for their ability to induce heterocysts in ammonia-repressed, undifferential filaments of Anabaena variabilis. As has been previously described, 1-methionine-dl-sulfoximine induces both heterocysts and nitrogenase. In contrast, dl-7-azatryptophan and beta-2-thienyl-dl-alanine were found to induce heterocysts but not nitrogenase activity (measured as acetylene reduction) even under microaerobic conditions. When the initial ammonium concentration was reduced, dl-7-azatryptophan-treated cultures sequentially produced heterocysts and then nitrogenase activity, but nitrogenase was detected only when a parallel culture without analog also became capable of acetylene reduction. Neither of the two latter analogs affected gamma-glutamyl transferase activity in crude extracts. All three analogs significantly reduced the mean interheterocyst distance in nitrogen-fixing cultures.